2021
DOI: 10.3389/fpsyg.2021.710167
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Effect of Parental Adult Attachment on Parent–Adolescent Attachment: The Mediating Role of Harsh Parenting

Abstract: This study examines the relationship between parental adult attachment and parent–adolescent attachment and investigates the mediating role of harsh parenting from the perspective of family systems theory. The sample included adolescents and their parents from 1,030 families in Henan Province, China. Measures included the Experiences in Close Relationships Scale, Inventory of Parent and Peer Attachment Scale, and Harsh Parenting Scale. The results showed that paternal avoidance negatively predicts father–adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Contrary to expectations, parental attachmentrelated avoidance was not found to be predictive of parentchild relationship quality in the current study. Li et al (2021) found that maternal anxiety negatively predicted the quality of relationship formed between mothers and their adolescent children, whilst maternal avoidance negatively predicted the quality of the relationship formed between fathers and their adolescent children. Given that most respondents in the current study were mothers, it is therefore not surprising that parental attachment-related anxiety predicted the quality of the relationship between these mothers and their adolescent children, whilst parental attachment-related avoidance did not.…”
Section: Discussionmentioning
confidence: 96%
“…Contrary to expectations, parental attachmentrelated avoidance was not found to be predictive of parentchild relationship quality in the current study. Li et al (2021) found that maternal anxiety negatively predicted the quality of relationship formed between mothers and their adolescent children, whilst maternal avoidance negatively predicted the quality of the relationship formed between fathers and their adolescent children. Given that most respondents in the current study were mothers, it is therefore not surprising that parental attachment-related anxiety predicted the quality of the relationship between these mothers and their adolescent children, whilst parental attachment-related avoidance did not.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, insecure parents are likely to have more difficulties in responding to their children sensitively and warmly. In the avoidance and anxiety style, parents tend to have more harsh parenting, which means more physical attacks, verbal attacks, and other crude behaviors or emotions towards their children [8]. The harsher the parenting style, the less attachment bond the parents build with their children.…”
Section: Parenting Stylesmentioning
confidence: 99%
“…Therefore, it is interesting to see how a father's adult attachment styles may impact the relationship within the family. In the study about the mediating role of harsh parenting that was carried out by Li et al, the researchers used Experiences in Close Relationships (ECR) questionnaires to collect data from approximately one thousand families of adolescents in the province of Henan in China [8]. According to the findings, adverse parent-adolescent attachment is more strongly associated with father avoidance and harsh paternal parenting than with insecure adult attachment and harsh parenting behavior of the mother.…”
Section: The Relationship Between Father's Different Parenting Aspect...mentioning
confidence: 99%
“…Regarding effectiveness, Allen et al (2016) stated that the only strong evidence is found in alcohol use prevention programmes. In contrast, Li et al (2023) affirmed that positive parenting results may be obtained independently of the format.…”
Section: Introductionmentioning
confidence: 98%